Living Qur’an in The Pesantren Campus: Religious Authority and Qur’anic Pedagogy at Ma’had Al-Jami’ah Uin Ar-Raniry, Indonesia - Fadhal Al Khalidi; Hasani Ahmad Said; Zahratul Farhah; Raudhatul Jannah; Rayyan Fitra Mulya; Suci Indah Putri (JURNAL INDO-ISLAMIKA, 2026)
This study examines how the Living Qur’an is practiced through religious authority and Qur’anic pedagogy at Ma’had Al-Jami’ah UIN Ar-Raniry, Indonesia. While Ma’had Al-Jami’ah has become a common institutional model in Indonesian Islamic higher education, its operation within Aceh’s distinctive socio-religious context offers an important case for understanding how pesantren-based Qur’anic formation is negotiated in a modern university. The study addresses the tendency to treat taḥsīn and Qur’anic learning primarily as technical processes of improving recitation, while overlooking their broader role in producing religious subjectivity, moral discipline, and embodied authority. Employing a qualitative case study design, the research draws on observation, semi-structured interviews with Ma’had administrators, Qur’anic teachers, students, and alumni, as well as institutional documentation and placement test data. The findings show that Ma’had Al-Jami’ah functions as an institutional space where the Qur’an is lived through taḥsīn, talqīn, taḥfīẓ, worship habituation, moral supervision, and emotional-psychomotor pedagogy. Religious authority is constructed through the teacher’s voice, correction, repetition, textual reference, and direct teacher-student interaction. The study also reveals that students’ Qur’anic literacy is uneven, shaped by prior educational backgrounds, institutional classification, learning duration, and everyday academic pressures. Theoretically, this article expands Living Qur’an studies by showing that Qur’anic reception is not only ritual or communal, but also institutional, pedagogical, embodied, and socially differentiated. It contributes to Qur’anic studies, lived Islam, pesantren studies, and Islamic higher education by demonstrating how the Qur’an becomes lived within the disciplined structure of a pesantren campus.